Real-world safety profile of the 9-valent human papillomavirus vaccine: A study in Zhejiang, China from 2019 to 2021 - Fuxing Chen; Xuejiao Pan; Hui Liang; Lingzhi Shen; Ying Wang; Yaping Chen; Huakun Lv; Yu Hu (Taylor & Francis Group, 2022)
The safety profile of the 9-valent human papillomavirus vaccine (9vHPV) was evaluated based on the reporting rate of adverse events following immunization (AEFI) obtained from the passive surveillance data in Zhejiang. The 9vHPV AEFI reports in Zhejiang were collected and reviewed from the National Adverse Event Following Immunization Surveillance System (NAEFISS) from 2019 to 2021. Reporting rates of AEFI were analyzed under multiple aspects, including age, city, number of vaccinations, AEFI categories, and diagnosis categories. This study used the reporting odds ratio (ROR) for anomalous signal assessment. The NAEFISS collected 331 AEFI reports after administering 1,064,851 doses of 9vHPV, with a crude AEFI rate of 3.12/10,000 doses. The third dose had the highest reporting rate of minor vaccine-related reaction (n = 80, 3.06 per 10,000), followed by the first dose (n = 134, 2.98 per 10,000), and second dose (n = 76, 2.15 per 10,000). Fever/redness/induration was the most common minor adverse event (281 records, 2.64/10,000 doses). Nine cases of urticaria, ten cases of allergic rash, and ten cases of syncope were recorded. This study found a positive signal association between 9vHPV immunization and adverse events such as syncope, encephalitis, sterile abscess, and urticaria. This study did not identify any new emerging safety concerns. In the future, more research is needed to validate and further explore adverse reactions associated with 9vHPV.